Strategic harmony in hospitality: the case of Multazam Syariah Hotel, Surakarta - Mhd. Sarif, Suhaimi; Abdul Sabian, Nur Arfifah; Juhdi, Nurita; Mustaffa, Nur Fariza; Hidayatullah, H. Rakhmad Agung; Riyanto, H. Agung (IIUM PRESS, 2026)
This case study examines the strategic trajectory of Multazam Syariah Hotel, a three-star Shariah-compliant establishment in Surakarta, Indonesia. Situated strategically near educational and religious institutions, the hotel was developed by the Tiga Serangkai Group to meet the increasing demand for ethical, family-orientated accommodation. Under the leadership of Haji Agung Riyanto, appointed General Manager in 2019, the hotel integrates Qur’anic values with professional hospitality management through distinctive leadership practices, rigorous human resource screening, and continuous religious education. The hotel’s Shariah certification from the Majelis Ulama Indonesia (MUI) and its adaptive strategies during the COVID-19 pandemic highlight its operational resilience and legitimacy within the halal tourism market. This case critically analyses the hotel's strategic establishment, leadership direction, human capital philosophy, and cultural cohesion, emphasising its faithbased differentiation as a source of sustainable competitive advantage. It also examines the strategic challenges and opportunities that the halal tourism industry faces as it grows. In a world where hospitality often mirrors secular business models, Multazam Syariah Hotel stands out as a pioneering example of integrating Qur’anic values with strategic managerial thinking. The hotel is not merely a place to stay; it is a symbolic convergence of faith and commerce, offering travellers a serene, ethical, and spiritually anchored environment. Its establishment near Islamic educational hubs in Surakarta is both opportunistic and visionary, aligning economic foresight with community service. Through this case, students are invited to explore how strategic positioning, religious ethics, and operational excellence can mutually reinforce each other to create a sustainable business model.